Associations Between Psychological Constructs and Cardiac Biomarkers After Acute Coronary Syndrome. Issue 3 (April 2017) - Celano, Christopher M.; Beale, Eleanor E.; Beach, Scott R.; Belcher, Arianna M.; Suarez, Laura; Motiwala, Shweta R.; Gandhi, Parul U.; Gaggin, Hanna; Januzzi, James L.; Healy, Brian C.; Huffman, Jeff C.
ABSTRACT: Objective: Psychological constructs are associated with cardiovascular health, but the biological mechanisms mediating these relationships are unknown. We examined relationships between psychological constructs and markers of inflammation, endothelial function, and myocardial strain in a cohort of post–acute coronary syndrome (ACS) patients. Methods: Participants ( N = 164) attended study visits 2 weeks and 6 months after ACS. During these visits, they completed self-report measures of depressive symptoms, anxiety, optimism, and gratitude; and blood samples were collected for measurement of biomarkers reflecting inflammation, endothelial function, and myocardial strain. Generalized estimating equations and linear regression analyses were performed to examine concurrent and prospective relationships between psychological constructs and biomarkers. Results: In concurrent analyses, depressive symptoms were associated with elevated markers of inflammation (interleukin-17: β = .047; 95% confidence interval [CI] = .010–.083]), endothelial dysfunction (endothelin-1: β = .020; 95% [CI] = .004–.037]), and myocardial strain ( N -terminal pro-B-type natriuretic peptide: β = .045; 95% [CI] = .008–.083]), independent of age, sex, medical variables, and anxiety, whereas anxiety was not associated with these markers in multivariable adjusted models. Optimism and gratitude were associated with lower levels of markers of endothelial dysfunction (endothelin-1: gratitude: β = −.009; 95% [CI] = −.017 to − .001]; optimism: β = −.009; 95% [CI] = −.016 to − .001]; soluble intercellular adhesion molecule-1: gratitude: β = −.007; 95% [CI] = −.014 to − .000]), independent of depressive and anxiety symptoms. Psychological constructs at 2 weeks were not prospectively associated with biomarkers at 6 months. Conclusions: Depressive symptoms were associated with more inflammation, myocardial strain, and endothelial dysfunction in the 6 months after ACS, whereas positive psychological constructs were linked to better endothelial function. Larger prospective studies may clarify the directionality of these relationships. Clinical Trial Registration: Clinicaltrials.gov identifier NCT01709669